Non-covalent interactions in quantum chemistry and physics theory and applications - Otero de la Roza, Alberto; DiLabio, Gino A. (Amsterdam Elsevier, 2017)
Non-covalent Interactions in Quantum Chemistry and Physics: Theory and Applications provides an entry point for newcomers and a standard reference for researchers publishing in the area of non-covalent interactions. Written by the leading experts in this field, the book enables experienced researchers to keep up with the most recent developments, emerging methods, and relevant applications. The book gives a comprehensive, in-depth overview of the available quantum-chemistry methods for intermolecular interactions and details the most relevant fields of application for those techniques. Theory and applications are put side-by-side, which allows the reader to gauge the strengths and weaknesses of different computational techniques.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction
Keywords: Quantum chemistry; Quantum theory; Electronic books